2022
DOI: 10.1177/15347354221132848
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety ofMorinda citrifoliaL. (Noni) as a Potential Anticancer Agent

Abstract: Cancer is a major cause of morbidity and mortality worldwide and therefore there has been interest in discovering the phytoconstituents of medicinal plants exhibiting anticancer activities. Morinda citrifolia L., commonly known as Noni, has shown anticancer properties in in vitro, in vivo, and in clinical studies. A systematic review was conducted to collate scientific evidence on the anticancer properties of M. citrifolia using pre-determined keywords on 5 electronic databases: MEDLINE, CENTRAL, LILACS, Web o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…M. citrifolia, also known as noni, is a tree or shrub in the Rubiaceae family with a pantropical distribution (Nelson 2003), which is abundant in the coastline of the province; and has found various beneficial effects due to its phytochemicals (Abou Assi et al 2017;Almeida et al 2019). Noni extracts have shown anticancer properties (Kumar et al 2022) and are not toxic or mutagenic, and have potential use in phytotherapeutic or nutritional contexts (de Matos Lima et al 2022).…”
Section: Beach Forests Flora Composition and Distributionmentioning
confidence: 99%
“…M. citrifolia, also known as noni, is a tree or shrub in the Rubiaceae family with a pantropical distribution (Nelson 2003), which is abundant in the coastline of the province; and has found various beneficial effects due to its phytochemicals (Abou Assi et al 2017;Almeida et al 2019). Noni extracts have shown anticancer properties (Kumar et al 2022) and are not toxic or mutagenic, and have potential use in phytotherapeutic or nutritional contexts (de Matos Lima et al 2022).…”
Section: Beach Forests Flora Composition and Distributionmentioning
confidence: 99%
“…Hence, exploring phytochemicals has led to the discovery of effective anticancer medications. Numerous plant species, such as the Azadirachta indica ( Moga et al, 2018 ) and Morinda citrifolia ( Chanthira Kumar et al, 2022 ), have shown the presence of anti-cancer capabilities in their respective floral components. Pomegranate ( Panth et al, 2017 ), brassinosteroids ( Panibrat et al, 2019 ), medicinal mushrooms ( De Silva et al, 2012 ), ginger extract ( de Lima et al, 2018 ), and turmeric extract ( Unlu et al, 2016 ), have been shown to possess qualities that might inhibit the growth and spread of cancer cells.…”
Section: Anticancer Potential: Muscadine Grape Skin Extract Vs Other ...mentioning
confidence: 99%
“…Vitamis (C, ascorbic acid, E, tocopherol etc.) are major non-enzymatic anti-oxidant that have main effects because of their free radical forage property [6].…”
Section: Antidyslipidemic Effect:-mentioning
confidence: 99%